China's Dual Identity and Its Discourse Toward the EU's Carbon Border Adjustment Mechanism - Joshua Kharizetha Evangelize Syauta (Journal Of Global Strategic Studies, 2025)
The European Union’s Carbon Border Adjustment Mechanism (CBAM) affects China’s export interests and provides a stage for identity performance in policy discourse. This article examines how China’s dual identity as a developing country and as a responsible major power structures its assessment of CBAM and its implied responses. Using qualitative content analysis with a MIC-mini coding scheme, the study analyzes 41 elite and semi-mass texts and translates four variables (Self, Other, Valence, Action) into comparable indicators, including the Identity Salience Index (ISI), Average Valence Score (AVS), and Action Orientation (AOR) under a 60 percent dominance rule. Findings show a stronger responsible major power framing in 2023, a persistently negative tone that becomes more legal and procedural, and action signals that shift from protest toward technical coordination. Developing country references persist, preserving flexibility between equity claims and rule-shaping. The study offers a replicable way to quantify identity in discourse and to link identity emphasis to tone and implied action.